Stress Anxiety and Sexual Dysfunction in Women Undergoing Infertility Treatment - Khan, Muhammad Muslim; Fatima, Fatima; Naila, Naila; Jamal, Izaz; Gul, Ijaz; Muneeb, Pirzada (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Infertility and its treatment represent a major life stressor for women, with profound psychological and interpersonal consequences. Recurrent treatment cycles, uncertainty regarding outcomes, financial burden, and sociocultural expectations contribute to heightened stress and anxiety. These psychological factors may negatively influence sexual function, further impairing emotional well-being and quality of life during infertility management. Objectives: To determine the frequency of stress, anxiety, and sexual dysfunction among women undergoing infertility treatment and to evaluate the association between psychological distress and impairment in sexual function. Methodology: This cross-sectional study will be conducted at a tertiary care infertility centre. Women undergoing medical or assisted reproductive treatments will be enrolled using non-probability consecutive sampling. Psychological distress will be assessed using the Perceived Stress Scale (PSS) and the anxiety subscale of the Hospital Anxiety and Depression Scale (HADS-A). Sexual function will be evaluated using the Female Sexual Function Index (FSFI). Sociodemographic characteristics, infertility duration, and treatment-related variables will be recorded. Data will be analysed using appropriate descriptive and inferential statistical tests. Results: 120 women undergoing infertility treatment, 78.3% reported moderate to high perceived stress and 36.7% had clinically significant anxiety. Sexual dysfunction (FSFI <26.55) was observed in 68.3% of participants and was significantly associated with higher stress, anxiety levels, longer infertility duration, and advanced treatment modalities (p < 0.05). Conclusion: Psychological distress and sexual dysfunction are common among women undergoing infertility treatment and are significantly interrelated. Incorporating routine psychological screening and integrated psychosocial support into infertility care may improve sexual health, emotional well-being, and overall treatment experiences.